Continuous thermosalinograph oceanography along RV METEOR cruise track M204 - Michael Schlundt; Ingo Grevemeyer (PANGAEA, 2025)
Underway temperature and salinity data was collected along the cruise track with two autonomous thermosalinograph (TSG) systems, each consisting of a SBE21 TSG together with a SBE38 Thermometer. Both systems worked independent from each other throughout the cruise. While temperature is taken at the water inlet in about 5 m depth, salinity is estimated within the interior TSG from conductivity and interior temperature. No correction against independent data was performed for temperature. Salinity was calibrated against independent water samples. Finally, TSG1 was chosen for publication. For details to all processing steps see Data Processing Report.